Nonuniform metal foam design and pore-scale analysis of a tilted composite phase change material system for photovoltaics thermal management. (15th September 2021) - Li, Xinyi; Duan, Jitong; Simon, Terrence; Ma, Ting; Cui, Tianhong; Wang, Qiuwang
Abstract: Photovoltaics, as a direct technology to convert sunlight into electricity, possess significant potential to deal with ever-increasing environmental problems and the desire to reduce the use of fossil fuels. Thermal stability of photovoltaics is of major concern when considering large-scale commercialization under conditions in which device degradation by high temperature operation is possible. Phase change materials (PCMs) are highly promising for thermal management of such devices due to their high latent heat and inherent heat transfer properties. However, a great challenge in applying PCMs to photovoltaics is in achieving high energy density while maintaining high power density, especially with different orientations of the photovoltaics. In this work, the dynamic heat transfer characteristics of a composite PCM with embedded metal foam are systematically studied by a pore-scale lattice Boltzmann model. It is found that the melting rate of composite PCMs dramatically decreases at late-stage melting, leaving a region of solid PCM ("dead zone") for a long time. To address this issue, we propose a special, nonuniform structure for the composite PCM that has a different porosity in the dead zone than elsewhere. The melting rate, energy density, and power density of the composite PCM can be significantly enhanced by tailoring the porosity of the composite metal foam. For instance, at a Fourier number of 0.30, the energy density of a case with a dead zone porosity of 0.80 is 6.8% higher than that with a dead zone porosity of 0.95. This work provides an effective strategy toward applying PCMs for thermal management of photovoltaics and paves a way toward optimizing energy storage capabilities of PCMs under various working conditions.